Giant multiloculated ameloblastoma of the mandible: a case report and review of literature - Virmani, Nitish; Dabholkar, Jyoti (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2016)
Ameloblastomas, in general, are considered benign but locally invasive neoplasms. They present as slow growing, painless swellings and can grow to enormous sizes over the years. While planning the treatment of ameloblastoma, it is important to understand the growth characteristics and removing the full extension of tumor, including the surrounding tissue. Recurrence of ameloblastoma in many cases reflects the inadequacy or failure of the primary surgical procedure. We report a case of giant multiloculated ameloblastoma of the mandible with destruction of the cortical plate and extensive and rapid infiltration of the buccal mucosa. Along with the clinical and imaging features, the importance and method of ruling out malignant ameloblastoma and ameloblastic carcinoma in such a case is discussed.